The implementation of the 5E model stages to build students' vocabulary - Muhammad Rochman (Journal on English as a Foreign Language, 2012)
There are stages of human to learn something. In early ages, they will learn simplest things to the complicated ones. A learning process of human is started with and introductory and it tries to connect with their prior knowledge to the new one. Children begin to curious about what they want to know and start to make some questions about what they want to know. In the process of finding the answers of their own questions, they will interact with others and try to share the knowledge in this process. The result of this study illustrates that the implementation of the 5E model in teaching vocabulary that can enhance the students’ vocabulary achievement and successfully encourages them to actively and enthusiastically take part in the teaching-learning process of vocabulary through group task.